2021
DOI: 10.1021/acschemneuro.1c00153
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Curcumin in Cerebral Ischemia: Cellular and Molecular Mechanisms

Abstract: Despite being a major global health concern, cerebral ischemia/stroke has limited therapeutic options. Tissue plasminogen activator (tPA) is the only available medication to manage acute ischemic stroke, but this medication is associated with adverse effects and has a narrow therapeutic time window. Curcumin, a polyphenol that is abundantly present in the rhizome of the turmeric plant (Curcuma longa), has shown promising neuroprotective effects in animal models of neurodegenerative diseases, including cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 106 publications
1
30
0
Order By: Relevance
“…The consumption of polyphenol-rich foods has been related to a lower risk of cardiovascular events (cardiovascular mortality, myocardial infarction, and stroke) and cardiovascular risk factors [ 87 ]. Curcumin, a polyphenol abundant in the rhizome of the turmeric plant (Curcuma longa), has shown promising neuroprotective effects in animal models of neurodegenerative diseases [ 88 ]. Curcumin could prevent mitochondrial dysfunction as it acts by enhancing the action of enzymes of the antioxidant defense system SOD, CAT, and GSH [ 89 ].…”
Section: Protective Effects Of Tcm and Its Constituent Compounds On I...mentioning
confidence: 99%
“…The consumption of polyphenol-rich foods has been related to a lower risk of cardiovascular events (cardiovascular mortality, myocardial infarction, and stroke) and cardiovascular risk factors [ 87 ]. Curcumin, a polyphenol abundant in the rhizome of the turmeric plant (Curcuma longa), has shown promising neuroprotective effects in animal models of neurodegenerative diseases [ 88 ]. Curcumin could prevent mitochondrial dysfunction as it acts by enhancing the action of enzymes of the antioxidant defense system SOD, CAT, and GSH [ 89 ].…”
Section: Protective Effects Of Tcm and Its Constituent Compounds On I...mentioning
confidence: 99%
“…Therefore, it is very effective in indirectly maintaining the redox balance in the central nervous system by regulating the Nrf2 pathway in glial cells ( Zhao et al, 2007a ). In vivo and in vitro studies have demonstrated that oral curcumin can inhibit the oxidative stress injury caused by ischemia—reperfusion, and this treatment can significantly reduce ROS in brain tissue and promote the expression of antioxidant genes ( Subedi and Gaire, 2021 ). This outcome may be due to curcumin-mediated activation of the Nrf/ARE pathway, thereby inhibiting oxidative stress ( Li et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin exhibits a wide spectrum of pharmacological effects including anti-microbial, anti-inflammatory, anti-oxidant, anticancer, anti-viral, and neuroprotective effects. The mechanisms of action of curcumin against various cancers and other disorders have been intensively reviewed, such as breast cancer (Hu et al, 2019), colorectal cancer (Pricci et al, 2020), lung cancer (Wan Mohd Tajuddin et al, 2019), cerebral ischemia (Subedi and Gaire, 2021), neurodegenerative diseases (Monroy et al, 2013), and diabetes (Pivari et al, 2019). An increasing body of evidence from clinical and experimental studies has shown the great potential of curcumin as anti-MM therapy.…”
Section: Active Components Derived From Tcmms For Multiple Myeloma Curcuminmentioning
confidence: 99%